2019
DOI: 10.15294/jpii.v8i1.17086
|View full text |Cite
|
Sign up to set email alerts
|

Language of Instruction Policy in Science Programs: Science University Students’ Voices

Abstract: The language of instruction policy in science university programs is chosen by different stakeholders. The voice of science university students (SUSs) has been neglected in many science programs around the world. A review of the literature shows that among all stakeholders, SUSs are influenced most-both positively and negativelyby the medium of instruction policy. This study analyzed the perspectives of 186 SUSs regarding the use of the country's official language as the medium of instruction (OLMI) and a fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The respondents believed that if Arabic is used as a medium of instruction, their GPA and exam performance will improve. These findings support Alhamami's (2019) qualitative results. Similarly, Hengsadeekul et al (2014) found that Thai university students were not interested to join discussions when English is the medium of instruction.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The respondents believed that if Arabic is used as a medium of instruction, their GPA and exam performance will improve. These findings support Alhamami's (2019) qualitative results. Similarly, Hengsadeekul et al (2014) found that Thai university students were not interested to join discussions when English is the medium of instruction.…”
Section: Discussionsupporting
confidence: 87%
“…Teachers can code-switch to translate complicated terms and new words into the students' native language. Alhamami (2019) emphasized that when instructors use the students' native language, they can cover the required learning outcomes because most science programs assume that learners are fluent in the language of instruction. Belhiah and Elhami (2015) suggested implementing a bilingual curriculum in which instruction M. Alhamami & A. Almelhi, The dilemma of English as a medium of instruction policy in science college programs | 1056 is delivered in English and Arabic to enhance linguistic and biliteracy skills, given that most students are not proficient in English.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations